2020
DOI: 10.3390/cancers12030620
|View full text |Cite
|
Sign up to set email alerts
|

RNA Immune Signatures from Pan-Cancer Analysis Are Prognostic for High-Grade Serous Ovarian Cancer and Other Female Cancers

Abstract: Immune cell infiltrates within the tumor microenvironment can influence treatment response and outcome in several cancers. In this study, we developed RNA-based immune signatures from pan-cancer analysis that could serve as potential markers across tumor types and tested them for association with outcome in high-grade serous ovarian cancer (HGSOC) and other female cancers. Pan-cancer RNA-Seq cluster analysis of immune-related gene expression profiles in The Cancer Genome Atlas (TCGA) from 29 different solid tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Besides, we found that EPB41L3, COL2A1, CYP1B1-AS1, and C9orf106 are all highly correlated with immune infiltration, which is consistent with various studies. For example, Wendell et al found that COL2A1 was bound up with cytotoxic lymphocyte immune signature and T-cell trafficking (51). It coincides with the finding of this study that there is a positive correlation between COL2A1 and naive CD4 T cells, confirming that COL2A1 is involved in the regulation of AML immune microenvironment.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, we found that EPB41L3, COL2A1, CYP1B1-AS1, and C9orf106 are all highly correlated with immune infiltration, which is consistent with various studies. For example, Wendell et al found that COL2A1 was bound up with cytotoxic lymphocyte immune signature and T-cell trafficking (51). It coincides with the finding of this study that there is a positive correlation between COL2A1 and naive CD4 T cells, confirming that COL2A1 is involved in the regulation of AML immune microenvironment.…”
Section: Discussionsupporting
confidence: 91%
“…With the development of high-throughput technologies, the omics sciences have advanced greatly, gaining unprecedented development; high-throughput methods have also promoted the progress of bioinformatics by generating thousands of massive datasets called “big data” ( 26 , 27 ). Thus, data mining has emerged to efficiently transform big data into useful information and knowledge, and several automated tools and techniques are used to intelligently assist data analysis ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…And Svetlana et al have found that the higher the tumor-infiltrating CD8+ T cells in EC patients, the higher the overall survival rate would be, which may be a very reliable independent prognostic factor (63). Jones et al have found that cytotoxic lymphocyte immune signature and T-cell trafficking signature were closely related to the prognosis of female malignancies such as EC, further confirming that immune cell infiltration in the tumor microenvironment affected survival and treatment outcomes in patients with EC (64).…”
Section: Discussionmentioning
confidence: 91%
“…Jones et al. have found that cytotoxic lymphocyte immune signature and T-cell trafficking signature were closely related to the prognosis of female malignancies such as EC, further confirming that immune cell infiltration in the tumor microenvironment affected survival and treatment outcomes in patients with EC ( 64 ).…”
Section: Discussionmentioning
confidence: 93%